Macroinvertebrados aquáticos associados à Eichhornia azurea (Swartz) Kunth e suas relações com as variáveis abióticas em ecossistemas lênticos marginais (São Paulo, Brasil) - Silva, C. V. [UNESP]; Henry, R. [UNESP] (FapUNIFESP (SciELO), 2013)
Marginal lakes are characterised by their having high biological diversity due to the presence of aquatic macrophytes in their coastal zones, providing habitats for refuge and food for animal community members. Among the fauna components associated with macrophytes, aquatic macroinvertebrates are important because they are an energy source for predators and fish. In six lakes and two different seasons (March and August 2009), the ecological attributes of aquatic macroinvertebrate community associated with Eichhornia azurea were compared and the controlling environmental factors were identified. Since the attributes of macroinvertebrate community are strictly associated with abiotic variables of each distinct habitat, our hypothesis was that each site associated with the same floating aquatic macrophyte (E. azurea) should have a typical composition and density of organisms. We identified 50 taxa of macroinvertebrates, with greater taxa richness for aquatic insects (37 taxa) divided into eight orders; the order Diptera being the most abundant in the two study periods. On the other hand, higher values of total taxa richness were recorded in August. Dissolved oxygen and pH presented the greatest number of significant positive correlations with the different taxa. The animals most frequently collected in the six lakes in March and August 2009 were Hirudinea, Oligochaeta, Hydrachnidae, Conchostraca, Ostracoda, Noteridae, Ceratopogonidae, Chironomidae, Culicidae, Caenidae, Pleidae, Aeshnidae, Libellulidae, Coenagrionidae and Nematoda. Only densities of Trichoptera, Ostracoda and Conchostraca presented the highest significant differences between lakes in both study periods and considering the composition of macroinvertebrates no significant differences were registered for macroinvertebrate composition.
Aquatic macroinvertebrates associated with Eichhornia azurea (Swartz) Kunth and relationships with abiotic factors in marginal lentic ecosystems (São Paulo, Brazil)
Keywords: Aquatic macrophyte; Marginal lakes; Phytofauna; fresh water; animal; aquatic species; biodiversity; Brazil; classification; ecosystem; Eichhornia; invertebrate; season; Animals; Aquatic Organisms; Biodiversity; Ecosystem; Fresh Water; Invertebrates; Seasons